DESIGNING ENGLISH LEARNING MATERIALS FOR INFORMATIC STUDY PROGRAM AT ENGINEERING FACULTY OF ISLAMIC UNIVERSITY OF LAMONGAN - Fita Faridah; Eko Sulistiono (E-LINK JOURNAL, 2018)
English learning is developing year by year through its method and every aspect in the learning process. The informatics study program has the main aim to develop the students’ intelligence, knowledge, personality, and skills in a workplace for having an independent life in their future. The relevant English learning materials for particular study programs are needed to facilitate the students to achieve good English proficiency. This research is aimed at developing English learning materials for the first semester of Informatics Study Program. The researcher applied Research and Development as the research method. In the research method the researcher implemented five of Borg and Gall’s Research and Development (R&D) stages. Then, those five stages were combined with Kemp’s theory of instructional model to develop and design the English materials, the steps included were: collecting the students’ need, planning, developing the materials, writing the final draft, and trying out the materials. Based on the research finding, the students learn English Learning material includes seven units and in every unit cover three Basic English competence reading, speaking and writing, and also consists of several sections, namely introduction, main lesson and reinforcement.